The Nexus between Social, Environmental, Law, Governance Dimensions and Economic Development for Indonesian’s SDGs Achievement - Rizka Zulfikar; Purboyo; Farida Yulianti; Lamsah; Aida Vitria (Ilomata International Journal of Management, 2023)
This study aims to identify the nexus between social, environmental, legal, governance dimensions and the economic development in order to achieve SDGS in Indonesia. The research uses quantitative methods with the primary data in the form of the SDGS Achievement indicators obtained from the 2015 to 2022 Indonesia National Planning Agency and Central Bureau of Statistics. The data analysis techniques are SEM-PLS bootstrapping, with confidence interval of 5%. The results showed that social, environmental, legal and governance development have a positive influence on economic development towards the achievement of the Sustainable Development goals. All the results of the t-test exceed 1.96, the P Values, which denote the level of significance required, are below 0.05, and the adjusted R Square has the value of 0.888 (88.8%), which suggests that its capability to clarify the correlation between social, environmental, law, governance and the economic development variable is robust, with an 88.8% level of accuracy. The implication of this research that economic growth has brought about many benefits for Indonesia, also proved to have significant impacts on various aspects of society, including the environment, social structures, law, and governance. It is critical to note that policymakers and stakeholders work together to address these challenges and to ensure that the development is sustainable and equitable for all Indonesians.